2012
DOI: 10.1159/000343340
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Support Proliferation and Terminal Differentiation of B Cells

Abstract: Background: Mesenchymal stem cells (MSC) play important roles in modulating the activities of T lymphocytes, dendritic cells and natural killer cells. These immunoregulatory properties of MSC suggest their therapeutic potential in autoimmune diseases. However, the effects of MSC on B cells are still poorly understood. The present study was designed to investigate the interaction between MSC and B cells both in vitro and in vivo, and to determine the possible mechanism of action. Design and Method: The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…Previous studies have shown that MSCs inhibit Th2-mediated allergic airway inflammation by promoting IFN-γ and TGF-β and regulating Th cell differentiation323334. MSCs are also known to modulate B-cell function35. Macrophages, which are the predominant immune effector cells, act as mediators of the inflammatory response and contribute to both the initiation and resolution of inflammation36.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MSCs inhibit Th2-mediated allergic airway inflammation by promoting IFN-γ and TGF-β and regulating Th cell differentiation323334. MSCs are also known to modulate B-cell function35. Macrophages, which are the predominant immune effector cells, act as mediators of the inflammatory response and contribute to both the initiation and resolution of inflammation36.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs from different perinatal sources have been shown to suppress T cell proliferation [54,58]. In contrast, interactions of perinatal MSCs with other cell types of the innate and adaptive immune systems are largely unknown with only limited number of reports available [59][60][61]. Results from studies comparing inhibitory effects of adult and perinatal MSCs on T cell proliferation are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MSCs suppress T-cell proliferation, shift Th1 cells toward Th2 cells [12], and inhibit differentiation of the Th17 subtype of CD4 + T cells [27]. Furthermore, MSCs support the proliferation and terminal differentiation of B cells [28]. MSCs significantly inhibit Th1 cell secretion of IFN-γ and TNF-α.…”
Section: Discussionmentioning
confidence: 99%